Katharine Vivian (1917-2010) - Marika Odzeli (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The English writer and translator Katharine Vivian was not only a wel-known Kartvelologist - translator of and researcher into Odl Georgian beles letres and historical writings but afriend of many representatives of Georgian intelligentsia of the second half of the 20 century and active participant of Kartvelological activity.